2021
DOI: 10.1007/s00702-021-02432-x
|View full text |Cite
|
Sign up to set email alerts
|

Blink reflex in newly diagnosed and treated patients with Wilson’s disease

Abstract: Abnormal blink reflex (BR) results mainly from the dysfunction of reticular brainstem pathways and is one of the features of degenerative brain disorders. We aimed to investigate whether patients with Wilson’s disease (WD) have abnormal BR. This was a prospective, observational, single-center study. BR was assessed in accordance with generally accepted standards in 44 newly diagnosed treatment-naïve and 66 treated patients with WD. Any abnormal parameters in BR were observed in 45.5% treatment-naïve patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…Although patients with a neurological presentation of WD typically develop extrapyramidal symptoms [8], other subclinical abnormalities have also been reported in motor-evoked potentials reflecting pyramidal tracts damage [20], somatosensory, auditory and visually-evoked potentials [21], visual pathways [22] and blink reflex [23]. Our study supports other reports which have suggested that, additionally, olfactory tracts may be affected in WD patients [11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…Although patients with a neurological presentation of WD typically develop extrapyramidal symptoms [8], other subclinical abnormalities have also been reported in motor-evoked potentials reflecting pyramidal tracts damage [20], somatosensory, auditory and visually-evoked potentials [21], visual pathways [22] and blink reflex [23]. Our study supports other reports which have suggested that, additionally, olfactory tracts may be affected in WD patients [11][12][13].…”
Section: Discussionsupporting
confidence: 89%